A multi-level memristor based on atomic layer deposition of iron oxide. (5th October 2018) - Porro, Samuele; Bejtka, Katarzyna; Jasmin, Alladin; Fontana, Marco; Milano, Gianluca; Chiolerio, Alessandro; Pirri, Candido Fabrizio; Ricciardi, Carlo
Abstract: This work reports the fabrication of memristive devices based on iron oxide (Fe2 O3 ) thin films grown by atomic layer deposition (ALD) using ferrocene as iron precursor and ozone as oxidant. An excellent control of the ALD process was achieved by using an experimental procedure based on a sequence of micro-pulses, which provided long residence time and homogeneous diffusion of precursors, allowing ALD of thin films with smooth morphology and crystallinity which was found to increase with layer thickness, at temperatures as low as 250 °C. The resistive switching of symmetric Pt/Fe2 O3 /Pt thin film devices exhibited bipolar mode with good stability and endurance. Multi-level switching was achieved via current and voltage control. It was proved that the ON state regime can be tuned by changing the current compliance while the OFF state can be changed to intermediate levels by decreasing the maximum voltage during RESET. The structural analysis of the switched oxide layer revealed the presence of nano-sized crystalline domains corresponding to different iron oxide phases, suggesting that Joule heating effects during I – V cycling are responsible for a crystallization process of the pristine amorphous layer.